2007
DOI: 10.1007/s00383-007-2064-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laparoscopic division of spermatic vessels on histological changes of testes: long-term observation in the model of prepubertal rat

Abstract: Laparoscopic Fowler-Stephens and Palomo procedures are now commonly performed in children with high positioned intra-abdominal cryptorchidism and varicocele, respectively. During the procedures, the spermatic vessels are ligated and therefore the question of risk related to testicular atrophy is often raised. The long-term follow-up of the histology after the procedures is rare. In this study, we simulated a laparoscopic spermatic vessels clipping and division (SVCD) in a prepubertal rat model, and examined th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This hypothesis was supported in our study by the frequent presence of fibrosis, dystrophic calcification, and hemosiderin deposition in the vanishing testis specimens. These pathological features are similar to the results of our previous animal experiment (15). Furthermore, as stated in our study and in other reports (5), testicular remnants are found more commonly on the left.…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis was supported in our study by the frequent presence of fibrosis, dystrophic calcification, and hemosiderin deposition in the vanishing testis specimens. These pathological features are similar to the results of our previous animal experiment (15). Furthermore, as stated in our study and in other reports (5), testicular remnants are found more commonly on the left.…”
Section: Discussionsupporting
confidence: 93%
“…Also, experimental studies in rats have raised concern about possible long-term deleterious effects of spermatic artery ligation on testis growth and development [29]. Spermatic artery-sparing surgical procedures have been developed but have led to persistent varicocele in 17% and hydrocele in 12.5% of patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IAT who have epididymo-testicular dissociation, the FSLO should not be performed, as a collateral vascular supply to the testis will not develop [27]. In rat studies, dividing the main testicular blood vessels results in atrophic changes in up to 51% of peri-pubertal rat testes [28]. It can be inferred that this is, therefore, not an optimal technique in humans and that preserving the main testicular vessels would be preferable.…”
Section: Discussionmentioning
confidence: 99%